MAINTENANCE PRIORITIZATION FOR AN INDUCTION FURNACE WITH ANALYTICAL HIERARCHY PROCESS IN PT. LINGGA SAKTI INDONESIA - Putra, Alvian Aries; Wulandari, Indah Apriliana Sari (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Abstract: The effective operation of induction furnaces in steel casting is crucial for maximizing production efficiency, yet equipment breakdowns remain a significant concern for manufacturers like PT. Lingga Sakti Indonesia. Despite existing maintenance strategies, there is a need for a more systematic approach to enhance Overall Equipment Effectiveness (OEE). This study addresses the knowledge gap in maintenance system optimization by employing the Analytical Hierarchy Process (AHP) to prioritize predictive maintenance tasks. The aim of this research is to assess the current OEE, calculated at 73.26%, and propose an updated maintenance framework based on the AHP findings, which involved input from four respondents across six criteria and nine alternatives. The results indicate that electrical monitoring emerged as the highest-ranked maintenance task, suggesting its implementation as a critical strategy for improving equipment reliability. The novelty of this approach lies in integrating AHP for maintenance decision-making, offering a quantifiable method for prioritizing tasks based on expert criteria. The implications of this study are significant, as the recommended maintenance system could enhance OEE and operational efficiency, ultimately leading to reduced downtime and improved productivity. Future research should focus on the practical implementation of these proposals and their impact on long-term maintenance effectiveness within the steel casting sector.